CONEXÃO DESCONECTADA: AS MÍDIAS DIGITAIS E SUAS IMPLICAÇÕES PARA O PROCESSO FORMATIVO - FIGUEIREDO, EDVALDO LUCAS DE (2019)
This study problematizes the issue of digital media, reflecting on its implications in the formative process, which is a great challenge for parents and educators. It defines the concepts of connected society and its relationship with technology and culture, explaining throughout the study the impacts of technology on the training process and the theoretical influences, as well as pointing ways to overcome the challenge of education in the context of this society. This theoretical effort instigates the discussion of accumulated knowledge and knowledge, so there is no criticism of technology, but attention is sought to the non-trivialization of knowledge, always valuing that methodological diversification is necessary, but should not be a slave to technology, mediatization or the cultural industry. The ideas of various authors who discuss the subject are presented, regardless of theoretical perspective. The paper also discusses how technology can influence education and training as a process that demands autonomy, based on Critical Theory. Changes and their repercussions on the teaching / learning process in the new educational context of digital natives are analyzed from the following aspects: the abundance of information, the ability to perform multiple tasks, knowledge, representation, communication, writing and reading the digital generation. Such elements constitute references for the discussion about the formative role of the teacher in the context of digital media.